Impact of a structured aquatic therapy program on patients with knee osteoarthritis - Kümpel, Claudia; Saadeddine, Islam; Porto, Elias Ferreira; Borba, Renata Gomes; Castro, Antônio Adolfo Mattos de (Acta Fisiátrica, 2016)
Osteoarthritis is a pervasive, chronic rheumatic, multifactorial, degenerative joint disease, afflicting 10% of the population over 65 years of age. It affects both genders, and in women the incidence is higher after menopause. This disease comprises 65% of the causes of disability, exceeded only by cardiovascular and mental disorders. The rehabilitation of patients with osteoarthritis is a complex process that involves specialized procedures Objective: To evaluate the effects of a hydrotherapy program on the ability to perform activities of daily living in patients with osteoarthritis. Method: This is a prospective study where twenty-six patients with knee osteoarthritis history underwent a treatment program in aquatic therapy, often twice a week lasting 50 minutes each session. The program consisted of four phases, namely: warming up, stretching, strengthening, and relaxation. These patients were evaluated before and after treatment. Assessments were done with the goniometer, EVA pain scale, and Six Minute Walk Test. Results: There was significant improvement in range of motion when performing flexion of the affected knees, as well as a significant decrease in pain and a significant improvement in the ability to perform the activities of daily living, assessed by the distance walked in the six-minute walk test. Conclusion: There was an improved ability to perform ADLs and inn physical capacity, as well as reduced pain and increased range of motion